SEASONAL INCIDENCE OF PROTOZOAN PARASITIC INFESTATION IN FRESHWATER FISHES OF AURANGABAD REGION (M.S), INDIA (International Journal of Food and Nutritional Sciences, 2022)
Present study deals with the prevalence of protozoan parasites of the freshwater fish of the Aurangabad region. During the study, more than seven hundred fish have been examined from different areas of the Aurangabad region during pre-monsoon, monsoon, and post-monsoon seasons. The highest protozoan infection has been recorded during post-monsoon seasoni.e., from October to January, followed by the monsoon period while the lowest infection was recorded during Pre-monsoon i.e. from February to May which may lead to the conclusion that environmental factors are responsible for spreading infection.